2005
DOI: 10.1021/ol052333c
|View full text |Cite
|
Sign up to set email alerts
|

A Total Synthesis of Tarchonanthuslactone Exploiting N-Pyrrole Carbinols as Efficient Stereocontrolling Elements

Abstract: [reaction: see text] A short stereoselective total synthesis of the polyketide natural product, tarchonanthuslactone, has been achieved. The key sequence involves the first reported catalytic enantioselective reduction of an N-acyl pyrrole and subsequent use of this stereocenter in a diastereoselective reductive cascade. This proceeded with unprecedentedly high stereocontrol and offered an elegant method of generating the desired syn stereochemistry present in the final target in one step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Tarchonanthuslactone ( 1 ) has a privileged structure, presenting the usually bioactive α,β-unsaturated δ-lactone motif [10,11,12,13], which makes it a good target for new asymmetric synthetic approaches [14,15,16,17,18]. Interestingly, Hsu and coworkers [19] have reported that caffeic acid ( 3 ) has an antidiabetic effect and, because of the structural similarity between 1 and 3 , a number of reports have, thereafter, assigned a putative antidiabetic effect to 1 as well [14,15,16,17,18,20,21,22]. Here, we employed a mouse model of diet-induced diabetes to evaluate the effect of 1 and related compounds (Figure 1) on blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…Tarchonanthuslactone ( 1 ) has a privileged structure, presenting the usually bioactive α,β-unsaturated δ-lactone motif [10,11,12,13], which makes it a good target for new asymmetric synthetic approaches [14,15,16,17,18]. Interestingly, Hsu and coworkers [19] have reported that caffeic acid ( 3 ) has an antidiabetic effect and, because of the structural similarity between 1 and 3 , a number of reports have, thereafter, assigned a putative antidiabetic effect to 1 as well [14,15,16,17,18,20,21,22]. Here, we employed a mouse model of diet-induced diabetes to evaluate the effect of 1 and related compounds (Figure 1) on blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…[47] Given the interesting and enabling features of N-acyl/ N-carbinol pyrroles, it is perhaps surprising that there are only a handful of instances in which such molecules have been employed in non-alkaloid natural product synthesis. [47,48] Vassilikogiannakis and coworkers have demonstrated that the photoinduced oxidation of furans can serve as a useful and enabling entry point for the construction of a variety polycyclic pyrrolidinone-containing heterocycles. [43] However, outside of this research group, these approaches remain rather underutilized in total synthesis.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…16). 62 The resultant chiral alcohol was then used in subsequent syn-syn reductions to direct the formation of several new stereocenters, and the pyrrolic ring was subsequently disassembled to give the non-pyrrolic target tarchonanthuslactone (79), a natural product isolated from the Trichonanthus trilobus tree. 63 A total synthesis of the myrmicarin alkaloids (Fig.…”
Section: Asymmetric Reductionmentioning
confidence: 99%